Rosenbergica 3.mezi hlavní městskou a venkovskou rezidencíkomunikace Petra Voka z Rožmberka s pražskými hospodáři (1594-1611) - Kubeš, Jiří (Univerzita Pardubice, 2003)
This article deals with the relationship between the last lord Rožmberk and his housekeepers in Prague in the times when Petr Vok spent only a few month a year in Prague or he did not travel to his main town residence in Prague at all (after 1603). In those times the housekeeper became a real head of Rožmberk administrative in Prague. Between 1594 and 1611 we know about 7 such officals. These were mostly men who tried to enrich from the Rožmberk's incomes. Petr Vok knew about the problems with his too much "independent" housekeepers and tried to find a way to make them fill all his orders. But the article shows that he did not succeed in his efforts because the position of his official bureaucracy was very strong and even an execution of one of the Prague housekeepers did not help him. At the end of his life he could only hope that the next hosekeeper would be more "faithful" and would follow his instructions. This "dream" was realized in a personality of Jan Libra who became the Prague housekeeper between 1605 and 1609.
Keywords: Rožmberkové; šlechtická sídla; města; urbanizace